Une chaîne d’extraction pour l’enrichissement de bases de données archéologiques - Frédérique Mélanie-Becquet; Johan Ferguth; Michel Cartereau; Katherine Gruel; Thierry Poibeau (Humanités Numériques)
This article focuses on an experiment aimed at extracting information from text in order to automatically feed databases in the field of archaeology. The first experiments concerned a set of books: the Cartes archéologiques de la Gaule (CAG). Knowledge transfer and meaning evolution phenomena were observed when thesauri were examined, since the same term can refer to different notions, and the same archaeological site may be categorised differently, at different points in time.